2005
DOI: 10.1590/s0102-76382005000300010
|View full text |Cite
|
Sign up to set email alerts
|

Fatores preditores de infarto do miocárdio no período perioperatório de cirurgia de revascularização miocárdica

Abstract: JAEGER, CP ET AL -Predictors of perioperative myocardial infarction in surgical myocardial revascularization

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 3 publications
2
8
1
Order By: Relevance
“…Jaeger et al [24] showed that 14% of patients presented perioperative AMI. The factors influencing the onset of AMI include: reoperation, injury to the left coronary artery, female gender [29], preoperative unstable angina, a higher number of grafts and prolonged cardiopulmonary bypass time [16,24,31,32,37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jaeger et al [24] showed that 14% of patients presented perioperative AMI. The factors influencing the onset of AMI include: reoperation, injury to the left coronary artery, female gender [29], preoperative unstable angina, a higher number of grafts and prolonged cardiopulmonary bypass time [16,24,31,32,37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The perioperative myocardial infarction can cause not only enzyme elevations without clinical relevance, as well as low cardiac output, malignant tachyarrhythmias and death [4,36,37,40]. Other factors are diabetes mellitus and hypertension [9, 24,25]. Mediastinitis is one of the most serious complications of median sternotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its value in diagnosis of myocardial infarction is well known in clinical patients, but it is still under study in patients already grafted, [1,[3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, it emphasizes the myocardial infarction (AMI) due to its high incidence, which varies from 5% to 15%, according to the literature. [1][2][3][4][5] The consequences of peri-operative AMI can vary from minor enzyme elevations without clinical relevance to presentations of low cardiac output or malignant tachyarrhythmias, followed by death or reduced long-term survival, which explains the efforts made in trying to avoid such complication [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%